The ROLE OF HUMAN DEVELOPMENT CADRES (KPM) IN STUNTING PREVENTION: A NONFORMAL EDUCATION PERSPECTIVE IN NORTH BENGKULU REGENCY - Agus Eko; Puji Yanti Fauziah; Yudan Hermawan; Zakky Muhammad Noor (Universitas Muhammadiyah Sidenreng Rappang, 2026)
Stunting remains a major challenge in human development in Indonesia, particularly in rural communities with limited access to health services and nutritional education. This study aims to analyse the role of Human Development Cadres (Kader Pembangunan Manusia/KPMs) in stunting prevention from a nonformal education perspective in North Bengkulu Regency. A qualitative case study approach was employed in Karang Anyar Village and Talang Pasak Village. Data were collected through in-depth interviews, observations, and documentation involving KPMs, health workers, village officials, and beneficiary families. The findings reveal that KPMs perform strategic roles not only as health programme implementers but also as facilitators of community learning, social mediators, and agents of behavioural change. Through participatory educational activities, home visits, and contextual nutritional assistance, KPMs contribute to improving community awareness regarding child nutrition and parenting practices. The effectiveness of their role is influenced by socio-cultural conditions, institutional support, and community participation. The study highlights the importance of strengthening communication and facilitation competencies to support sustainable community-based stunting prevention.